Features of The Managing Style of Cadets Depending On the Role Model of the Commander Chosen by Them - Василий И. Иванов; Юлия М. Перевозкина; Михаил И. Федоришин (Rossijskij psihologičeskij žurnal., 2023)
Introduction. Purpose of the article involves determining effective role models in solving military-professional tasks and identifying the features of the management style with the expression of various role models of the commander.  Methods. Research design included solving by cadets (N = 150, at age 21 to 27 years) 9 service and combat tasks, distributed in three blocks. In the process of solving the introductory task, the cadet had to choose a role model out of 10 possible ones, with which he identifies himself as a commander. For each block, the most frequently encountered roles of the cadet commander were identified, which were presented as dominant. All cadets were tested on the questionnaire "Management style" using the program "Psychologist-BB", on the basis of which the cadet was awarded points in three management styles. To determine the dependence of the management style on the leading role model, a one-factor analysis of variance (ANOVA) was performed. Results. Analysis showed a statistically significant influence of the chosen role model of the commander of the authoritarian and liberal management style when performing tasks aimed at stabilizing interpersonal relations during the organization of service and combat activities and making decisions in an unusual situation. Discussion. The results obtained indicate that cadets, when solving military-professional tasks related to the normalization of interpersonal relations during the organization of service and combat activities, personnel injuries and non-standard situations, choose mainly three role models of the commander as the role of the commander, which correspond to: role model 1 with a democratic management style, role model 2 with an authoritarian management style and role model 3, with two management styles – active and passive.